Islamization of Monetary Policy of 27 OIC Muslim Countries in Asia: The Successes, The Barriers and The Future Directions - Basharat Hossain (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2019)
The Islamization of banking, monetary policy, and the financial system began in 1975 after the setup of the Islamic development bank (IDB). Firstly, this paper discusses a concise framework of Islamic monetary policy. Then it presents the success and obstacles of the Islamization process of the monetary policy among the 27 OIC member Muslim countries in Asia and provides future directions to enhance the Islamization process. This paper employed secondary data and used the three criteria to measure the Islamization process: 1) Islamization of commercial banking; 2) making Islamic banking guidelines & regulations; 3) innovation and starting the Islamic monetary policy instruments. This paper finds that more than 154 Islamic commercial banks are operating under the Conventional monetary policy in 23 countries with very few Islamic monetary tools. On the contrary, Iran follows full-pledged Islamic monetary policy with 30 Islamic commercial banks. More precisely, in these countries, only 17% of total banks are Islamic bank, whereas 83% are still interest-based banks. Regrettably, two countries (Turkmenistan and Uzbekistan) do not have any tools of Islamic monetary policy. This paper also finds that though 64% of Islamic banks were established during 1970-2000 periods in 27 countries, only 25% of countries prepared Islamic banking regulation at this period. On the other hand, 75% of Islamic banking regulations were made during 2000-2015 periods. Most common Islamic monetary instruments are project-based Sukuk, project-based debt instruments, etc. Finally, this paper recommends six steps to enhance the Islamization process.